Eksplorasi Potensi Hasil Hutan Bukan Kayu Tanaman Tarum ((Indigofera tinctoria L) Sebagai Pewarna Alami Kain Tenun Di Kabupaten Malaka, Provinsi Nusa Tenggara Timur - Anaci Cornelia Imeldanita; Adrin Adrin; Aah Ahmad Almulqu (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This research was carried out in July-August 2022 in Biau Village, Io Kufeu District, Malaka Regency. This study aims to determine the potency and distribution of the tarum plant (Indigofera tinctoria L.) and the impact of tarum leaf size on the resulting color. The research method used in this study is the method of exploration, inventory and ethnobotany. The samples in this study were tarum plants and the people who were members of the weaving group. The data obtained from this study were analyzed using descriptive statistical analysis. The results of this study indicate that the potential and distribution of the tarum plant, found (50) growing points of the tarum plant which are widespread in the Biau village area with the average value of the tarum plant having (59.78) branches, crown circumference (374.26) ) cm, plant height (280.74) cm, plant pods (1.033) pods and plant leaves as many as 961 leaves. While the impact of the size of the leaves on the resulting color is that the black color is produced from the use of tarum leaves as much as 2.224 kg (100%), the blue color is produced from the use of tarum leaves (75%) and the gray color is produced from the use of tarum leaves (50%).